Stimulation Versus Inhibition-Bioactivity of Parthenin, a Phytochemical from L. - Regina G. Belz (SAGE Publishing, 2008)
Parthenium hysterophorus L. is an invasive weed that biosynthesizes several phytochemicals. The sesquiterpene lactone parthenin receives most attention regarding allelopathy of the plant or potential herbicidal properties. Since parthenin exhibits dose-dependent phytotoxicity with low dose stimulation, this study investigated the occurrence and temporal features of parthenin hormesis in Sinapis arvensis L. sprayed with parthenin under semi-natural conditions. Dose/response studies showed that the occurrence and the magnitude of hormesis depended on climatic conditions and the parameter measured. Within the tested dose range, stimulatory responses were only observed under less-stressful conditions and were most pronounced for leaf area growth [138 % of control; 13 days after treatment (DAT)]. Temporal assessment of leaf area development showed that doses causing a stimulatory response at the end of the experiment (< 0.42 ± 0.04 kg/ha; 13 DAT) were initially inhibitory up to ED 50 values (2 DAT). This clearly demonstrated an overcompensatory response. Inhibition of leaf area at 13 DAT reached ED 50 values on average at 0.62 ± 0.12 kg/ha, and S. arvensis was completely inhibited at doses exceeding 1.81 ± 0.56 kg/ha (ED 90 ). Based on these findings, implications of parthenin hormesis are discussed with respect to allelopathy of P. hysterophorus and exploitation of growth stimulatory responses in agriculture.